THE IMPLEMENTATION OF VIDEO TO IMPROVE STUDENTS ABILITY IN WRITING PROCEDURE TEXT AT XI CLASS SMA SWASTA DARUL IMAN IN ACADEMIC YEAR 2021/2022 - ELVIANA DAMAYANTIA; MUHAMMAD TAHIR; RAJA FAUZIAH (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
This study deals with the use video to improve students’ procedure text writing class XI SMA Swasta Darul Iman Academic Year 2021/2022. Its objective is to find out whether the use video has a significance effect in writing procedure text. Population used in this study of class XI and samples used in this study were 64 students. The method used in this study is an experimental method with a one group as pre-test and post-test design. This study was carried on using quantitative method. The data was analysed by using t-test. The researcher found the pre-test mean = 55,39 , deviation standard = 3,26 and experienced an increase in the post-test mean = 80,31 deviation standart = 3,66.From this analysis, writer found that guided video has significane in teaching writing procedure text. It can be proved by the result of the analysis showed that “” observed about 40,85 was higher than “t-table” about 1,998 with the level significance is 0,05% it implies that the teacher of English should use video in teaching writing procedure text so that the teaching and learning process can be successful.